2018
DOI: 10.1109/tgrs.2018.2798705
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetry-Based Distributed Scatterer Processing Method for PSI Applications

Abstract: Permanent scatterer interferometry is a multitemporal interferometric synthetic aperture radar technique that produces high-accuracy ground deformation measurement. A high density of permanent scatterer (PS) is required to provide accurate results. In natural environments with low PS density, distributed scatterers (DSs) could serve as additional coherent observations. This paper introduces a polarimetric scattering property-based adaptive filtering method that preserves PS candidates and filters DS candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…As more and more sattelites with the capability of acquiring PolSAR images (e.g., Radarsat-2, ALOS-2, TerraSAR-X, and Sentinel-1) have been launched, it is possible to extend the PolPSI techniques from the Ground-based SAR images to satellite SAR images. Under this circumstance, more PolPSI algorithms have been proposed [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…As more and more sattelites with the capability of acquiring PolSAR images (e.g., Radarsat-2, ALOS-2, TerraSAR-X, and Sentinel-1) have been launched, it is possible to extend the PolPSI techniques from the Ground-based SAR images to satellite SAR images. Under this circumstance, more PolPSI algorithms have been proposed [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…It can effectively make up for the shortcomings of the ADI+ESPO and select PSCs more effectively. The performance of the ESPO has been discussed in [22,23,34]. In the experiment in this paper, we also found that the EPSO method can suppress the side lobe effect to a certain extent, and the texture of the surface coverage is clearer.…”
Section: Comparison Of Different Psc Selection Methodsmentioning
confidence: 57%
“…The quad-polarimetric observation information of the scattering target can be denoted by the complex scattering vector k. In order to obtain the interferometric phase and coherence of quad-polarimetric images, we need to convert k to µ using unitary complex vector ω [23]:…”
Section: Polarimetric Optimization Of Psc Using Exhaustive Search Polmentioning
confidence: 99%
See 1 more Smart Citation
“…In Engelbrecht et al [31], the authors demonstrated that the adding value of the multiple scattering mechanisms approaches in L-band ALOS PalSAR enhances the ability to extract deformation measurements in dynamic agricultural regions. Recently, an attempt has shown that the adding value of polarimetric information can lead to the increase of the number of coherent pixels by a factor of eight with respect to a single-polarization channel [33].…”
Section: Overview Advancementsmentioning
confidence: 99%